2019
DOI: 10.3390/nu11030498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Primary Care Weight Management Program in Children Aged 2–5 years: Changes in Feeding Practices, Health Behaviors, and Body Mass Index

Abstract: Background: Primary care offers a promising setting for promoting parenting practices that shape healthy eating and physical activity behaviors of young children. This study assessed the impact of a parent-based, primary care intervention on the feeding habits, health behaviors, and body mass index (BMI) of 2–5 year olds with elevated or rapidly-increasing BMI. Methods: Four private pediatric offices in West Michigan were assigned as control (n = 2) or intervention (n = 2) sites based on patient load and demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 57 publications
0
55
0
Order By: Relevance
“…On the contrary, several studies have evaluated them in childhood obesity management (or weight management) in home-based or primary care settings. Tucker, DeFrang, Orth, Wakefield, and Howard (2019) reported that a six-month parent-based weight management programme showed a significant effect on improving FNPA scores, but not on children's BMI in primary care settings [51]. Reportedly, higher FNPA scores were positively associated with children's healthy eating behaviors and negatively associated with children's obesity status [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, several studies have evaluated them in childhood obesity management (or weight management) in home-based or primary care settings. Tucker, DeFrang, Orth, Wakefield, and Howard (2019) reported that a six-month parent-based weight management programme showed a significant effect on improving FNPA scores, but not on children's BMI in primary care settings [51]. Reportedly, higher FNPA scores were positively associated with children's healthy eating behaviors and negatively associated with children's obesity status [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1596 articles were searched from each database, 1585 articles were excluded according to the inclusion and exclusion criteria. Finally, 11 articles were included in this study [31,[38][39][40][41][42][43][44][45][46][47]. (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…All of included studies were published in 2012 or later, among which 7 were published in 2015 or later. Of them, 4 studies from Australia [38,40,45,46], 3 from the United States [31,42,44]. The United Kingdom [47], Germany [43], Finland [41], Norway and Sweden [39] each have one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations